OPTIMIZING REFUGIA PLANTING AREAS AND INCREASING THE FREQUENCY OF PREDATOR SIGHTINGS CAN INCREASE ENVIRONMENTALLY FRIENDLY AND SUSTAINABLE RICE PRODUCTION - Holidah Fauziah; Irpan Sudirman; Rahmat Gunawan; Wachdijono Wachdijono (Riviera Publishing, 2025)
Efforts to increase rice production in Indonesia are crucial due to the country’s large population and heavy reliance on rice as a staple food. While chemical pest control has been widely used, it is costly and harmful to the environment. Therefore, alternative eco-friendly approaches, such as utilizing refugia plants and predators, are needed. This study aims to analyze the influence of refugia plants on predator presence and their impact on rice production. The research is conducted in Maleber, Kuningan Regency, West Java, Indonesia. Primary data collection takes place from July to December 2024, with processing in January 2025. This quantitative study employs a survey method with 120 randomly selected farmers who use refugia plants in rice cultivation. Data is analyzed using Structural Equation Modeling (SEM) with AMOS. The findings indicate a complete mediation effect, where refugia plants significantly influence predator presence (0.93), which in turn positively affects rice production (0.97). The most dominant indicator in refugia variables is the embankment area allocated for refugia planting (0.86), while in predator variables, it is the frequency of predator sightings (0.86). These results suggest that environmentally friendly and sustainable rice production can be improved by optimizing embankment areas for refugia planting and enhancing predator populations in rice fields.